NEGOTIATE THE DIVERSITY A Study on the conservation of Local Cultural Wisdom in the Cohesion and Segregation of Society at Asahan Regency and Toba Samosir Regency - Ismet Sari; Endang Ekowati (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
Indonesian society, which is diverse and has diverse cultural backgrounds, clearly needs a frame of reference to hold on to the current national association. Therefore, traditional values that contain wisdom, equality, multiculturalism, and can be used as a common grip for all Indonesian people wherever they live, need to be explored and researched and then offered as a good alternative for the development of new and harmonious socio-religious life . Empirical facts show that one of the causes of conflict is the non-functioning of the values of local cultural wisdom. Therefore, local cultural wisdom is important to use in renegotiating conflicts. This awareness stimulates the implementation of various studies or studies on the wisdom of local ethnic cultures. Through studies or studies, it has been found and recognized local ethnic cultural wisdom that is used as an instrument in creating, maintaining, and strengthening harmony and preventing and resolving social conflicts that occur in the community. Because of that fact, pluralism in a broad sense is a reality that cannot be avoided. In the realm of political theory, experts try to find a system that is able to manage differences fairly and peacefully. While in the cultural sphere, interaction with others naturally will result in a synthesis of culture and social practice which is a fusion of cultural diversity that takes place in a conducive and open public space. Public space that is conducive and open to a variety of views, streams and culture that is embraced by citizens will provide an opportunity for the community to negotiate differences peacefully and fairly. Keywords: The conservation of Local Cultural Wisdom, the Cohesion and Segregation of Society, Asahan Regency, Toba Samosir Regency